Knowledge on national immunization program and its associated factors among parents in Dungun, Terengganu - Fauzi, Tengku Muhammad Fakhruddin Tengku Md (2020)
In recent years, children are still unvaccinated, and vaccine-preventable disease outbreaks still occur. These situations remain despite an excellent national immunisation programme. Misinformation circulated on the internet as well as other outlets about vaccine safety. Thus, parental knowledge of immunisation programmes also affected immunisation uptake compliance, as parents are the primary decision-makers. Necessary information on parents' socio-demographic characteristics and knowledge of immunisation programmes will enable successful public health intervention. This project aimed to determine the levels of knowledge on the National Immunization Programme (NIP) and to determine the associated factors for the poor knowledge among parents in Dungun, Terengganu. This was a cross-sectional study. Data was collected using an interviewer-guided validated questionnaire. There are 404 respondents selected from a systematic random sampling method from each health clinics in Dungun. From 404 respondents selected, only 375 agreed to participate in this study. Descriptive analysis, simple and multiple logistic regression were used to test the objectives using IBM SPSS version 24.0. Majority of the respondents (50.4%) were categorized as having poor knowledge on National Immunization Programme while 186 respondents (49.6%) were categorized as having good knowledge on National Immunization Programme based on their total mark score. Factors that found to be significantly associated with poor knowledge were low educational status (aOR= 1.92; 95% CI: 1.25,2.95; p= 0.003) and parents age group 30-40 years old (aOR= 0.56; 95% CI: 0.34,0.93; p= 0.027). This study revealed that efforts are still required to enhance parents’ knowledge regarding childhood immunization awareness. Based on this study majority of the respondent still have poor knowledge regarding immunization program in Malaysia. The result has shown that the age of parents and their level of education are significantly associated with poor knowledge regarding immunization program. Effective education programs or immunization campaigns shall be designed to target high-risk populations.